COVID-19: Pulmonary and Extra Pulmonary Manifestations - Elrobaa, Islam H.; New, Karl J. (Frontiers in Public Health, 2021)
Introduction: The coronavirus disease (COVID-19) pandemic has been the most significant event in 2020, It is a highly infectious disease, wherein the virus (severe acute respiratory syndrome coronavirus 2) rapidly multiplies and spreads to all parts of the body. Therefore, COVID-19 is not only a respiratory disease but also a multi-system disease. Many people including physicians incorrectly believe that the disease affects only the respiratory tract. In this study, we aimed to describe COVID-19 manifestations and the underlying pathophysiology to provide the readers with a better understanding of this disease to achieve good management and to control the spread of this disease. Methods: Secondary data were obtained from the PubMed, Google Scholar, and Scopus databases. The key words used for the search were as follows: COVID-19, COVID-19 pulmonary manifestations, COVID-19 extra pulmonary manifestations and pathophysiology of COVID-19. We collected secondary data from systemic reviews, meta-analyses, case series, and case reports in the form of public data published on websites of the government, medical corporations, medical peer-reviewed journals, and medical academies all were indexed in PubMed, Google Scholar, or Scopus. Our questions were [Is COVID-19 a respiratory disease only? and [What are the extrapulmonary manifestations of COVID-19? Results: From our data, we found that a patient with COVID-19 may be either asymptomatic or symptomatic. Symptomatic cases may have either pulmonary or extrapulmonary manifestations. Pulmonary manifestations occur as mild, moderate or severe cases. In the mild and moderate cases, extrapulmonary manifestations such as gastroenteritis, fever, or vomiting may present alone. Some of these cases may be missed for diagnosis, and the patient may receive symptomatic treatment without a COVID-19 diagnosis, leading to increased spread of the infection. Extrapulmonary manifestations may occur in severe and critical cases as complications of severe infections [high viral overload] or the cytokine storm such as in acute kidney injury , heart failure (HF), and venous thromboembolic manifestation. Conclusions: COVID-19 is not a respiratory disease alone; rather, it is a multisystem disease. Pulmonary and extra-pulmonary manifestations should be considered for the early diagnosis and control of the spread of the infection.